Очистка води від нікелю за допомогою виробничих відходів - Зоря, О. В.; Терновцев, О. В. (Ways to Improve Construction Efficiency, 2013)
The technological scheme to purify the nickel containing sewage using ferromagnetic with nickel regeneration is the thesis principal result.